AN EVALUATION OF ACCOUNTING INFORMATION SYSTEM AND DEVELOPMENT OF FINANCIAL QUATERLY REPORT (FQR) REPORTING PROCESS - Muljo, Hery Harjono; Wulandari, Wulandari; Noerlina, Noerlina (Bina Nusantara University, 2023)
This study aims to evaluate the results of the implementation of an Accounting Information System (AIS) which has been implemented by a consulting firm, focusing on the reporting processes at a Joint Venture company named Blue Water. Blue Water is an oil and gas exploration company. The evaluation method used is a Fit/Gap Analysis. The evaluation is only performed for the exploration and development stage of petroleum operations. From the results of the Fit/Gap Analysis, a gap in meeting the reporting requirements of the Indonesian Host Government (HG) was identified. Specifically, the HG requires that oil and gas contracting companies submit FQR to the Special Taskforce for Upstream Oil and Gas Business Activities, named SKK Migas. To overcome this gap, the author has constructed a business intelligence platform which extracts information from the AIS into a data model and enables reporting in the format required by the FQR. The data model also includes information which is outside the AIS. The data model is updated automatically with real-time information; it uses a powerful formula language for the analytics and uses the familiar user interface of Microsoft Excel.